KAJIAN KUALITAS COOKIES AMPAS KELAPA (Quality Assessment of Coconut Fibres Cookies ) (UPN VETERAN JAWA TIMUR, 2015)
Abstract Cookies is a kind of snack made from baked soft dough with containing high fat, crisp and when broken fragment of less dense-textured cross section. Cookies on the market have very low fiber content, so in this study added flour coconut dregs (containing 12% crude fiber). The addition of coconut fibres cause flour cookies become hard, necessitating the addition of egg yolks to improve crispness cookies and also serves as an emulsifier. This research aims to know the influence of proportion of wheat flour coconut fibres flour and the addition of egg yolks to the characteristic of the physical, chemical and organoleptic coconut cookies. This study used a Factorial Complete Randomized Design consisting of 2 factors with 2 replications, the first factor is the proportion of wheat flour : coconut dregs flour (100: 50; 100: 100; 50: 150) and second factor is the addition of egg yolks (120; 130; 140 grams).The results showed that the best treatment on the proportion of wheat flour flour coconut dregs: 100: 100 and the addition of egg yolk 140 grams, which produces coconut cookies with moisture content = 4,018% protein = 9,212%, fat content = 17,232%, crude fibre content = 11,683%, texture = 0,458 mm grams/sec and organoleptic flavor 4,55/(love-love), color 4.25/(like-like) texture 4.6/(like-very like) Keyword : cookies, coconut fibres flour, egg yolks Abstrak Cookies merupakan jenis makanan ringan yang dipanggang yang terbuat dari adonan lunak yang berkadar lemak tinggi, renyah dan bila dipatahkan penampang potongannya bertekstur kurang padat. Cookies di pasaran kandungan seratnya sangat rendah, sehingga pada penelitian ini ditambahkan tepung ampas kelapa (yang mengandung 12% serat kasar). Penambahan tepung ampas kelapa menyebabkan cookies menjadi keras, sehingga perlu penambahan kuning telur untuk meningkatkan kerenyahan cookies dan juga berfungsi sebagai emulsifier. Penelitian ini bertujuan untuk mengetahui pengaruh proporsi tepung terigu:tepung ampas kelapa dan penambahan kuning telur terhadap sifat fisik, kimia dan organoleptik cookies kelapa.Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) pola faktorial yang terdiri dari 2 faktor dengan 2 kali ulangan, faktor I adalah proporsi tepung terigu:tepung ampas kelapa (100:50; 100:100; 50:150) dan faktor II adalah penambahan kuning telur (120; 130; 140 gram).Hasil penelitian menunjukkan bahwa perlakuan terbaik terdapat pada proporsi tepung terigu:tepung ampas kelapa 100:100 dan penambahan kuning telur 140 gram, yang menghasilkan cookies kelapa dengan kadar air= 4,018% kadar protein =9,212%, kadar lemak= 17,232%, kadar serat kasar= 11,683%, tekstur = 0,458 mm gram/detik dan uji organoleptik rasa 4,55/(suka-sangat suka), warna 4,25/(suka-sangat suka) tekstur 4,6/(suka-sangat suka). Kata kunci : cookies, tepung ampas kelapa, kuning telur